PLANNING FOR PUBLIC STREET LIGHTING (PJU) BASED ON SOLAR POWER SPREADED IN PUBLIC FACILITIES AREAS - Hais, Yosi Riduas; Ramades, Rudi; Manab, Abdul (-, 2024)
Planning for Public Street Lighting (PJU) with Solar Power Plants (PLTS) consists of identifying the location of PJU points, analyzing energy needs, choosing the right components and RAB. Take into account factors such as light intensity and environmental conditions at Jambi University, because at Jambi University there are still many PJUs that lack lighting and some are completely dead. This planning aims to create an efficient and sustainable system such as Careful selection of materials, technical design and financing are key steps in ensuring the successful implementation of PJU PLTS planning, which will ultimately provide the benefits of environmentally friendly and energy efficient street lighting. The data collection location was in the Jambi University campus area, a field study was carried out to determine the lighting needs in PJUs. The measurement results were analyzed by referring to PUPR Ministerial Regulation Number 25/PRT/M/2022 concerning street lighting specifications in urban areas, knowing how many panels will be used, measure the width of the main road and to measure the width of the green open space, design the PJU PLTS design and calculate the RAB to describe the installation that will be used in the planning that will be carried out. The results of the design planning for 1 lane PLTS PJU and 2 lane PLTS PJU with different heights, 1 lane PLTS PJU has a height of 7 meters while 2 lane PLTS PJU has a height of 12 meters, 1 lane PLTS PJU and 2 lane PLTS PJU also have differences in the distance between lights, 1 lane PLTS PJU, the distance between lights is 1.5 meters and 2 lane PLTS PJU, the distance between lights is 3 meters. The two PLTS PJUs both use concrete foundations because the concrete foundation has very great strength so that it can withstand the load of the PLTS PJU poles well and the total RAB required for planning the PLTS PJUs requires funds of IDR 1,509,816,000.